Cardiac Metastases in Neuroendocrine Tumors: 68Ga-DOTATATE PET/CT With Cardiac Magnetic Resonance Correlation. (April 2020) - Polk, Stuart Lane; Montilla-Soler, Jaime; Gage, Kenneth L.; Parsee, Arthur; Jeong, Daniel
Abstract : Abstract: Neuroendocrine tumor (NET) cardiac metastases can be associated with complications including ventricular outflow obstruction, arrhythmias, heart failure, and cardiac arrest, warranting intervention. Anatomical characterization of these lesions via cardiac magnetic resonance (CMR) is helpful to assess and predict the risk of complications and guide therapy. Images of 2 patients with small bowel NET related cardiac metastases are described on 68 Ga-DOTATATE PET/CT and CMR. The lesions were significantly smaller and more obscure on CMR compared with PET/CT. On CMR, T2-weighted dark blood images and late gadolinium enhancement images offered the most conspicuous detection of the NET myocardial metastases in these cases.